Heme Oxygenase, Inflammation, and Fibrosis: The Good, the Bad, and the Ugly? - Lundvig, Ditte M. S. (Frontiers Research Foundation, 2012)
Upon injury, prolonged inflammation and oxidative stress may cause pathological wound healing and fibrosis, leading to formation of excessive scar tissue. Fibrogenesis can occur in most organs and tissues and may ultimately lead to organ dysfunction and failure. The underlying mechanisms of pathological wound healing still remain unclear, and are considered to be multifactorial, but so far, no efficient anti-fibrotic therapies exist. Extra- and intracellular levels of free heme may be increased in a variety of pathological conditions due to release from hemoproteins. Free heme possesses pro-inflammatory and oxidative properties, and may act as a danger signal. Effects of free heme may be counteracted by heme-binding proteins or by heme degradation. Heme is degraded by heme oxygenase (HO) that exists as two isoforms: inducible HO-1 and constitutively expressed HO-2. HO generates the effector molecules biliverdin/bilirubin, carbon monoxide, and free iron/ferritin. HO deficiency in mouse and man leads to exaggerated inflammation following mild insults, and accumulating epidemiological and preclinical studies support the widely recognized notion of the cytoprotective, anti-oxidative, and anti-inflammatory effects of the activity of the HO system and its effector molecules. In this review, we address the potential effects of targeted HO-1 induction or administration of HO-effector molecules as therapeutic targets in fibrotic conditions to counteract inflammatory and oxidative insults. This is exemplified by various clinically relevant conditions, such as hypertrophic scarring, chronic inflammatory liver disease, chronic pancreatitis, and chronic graft rejection in transplantation.